Pilot study of the pharmacokinetics of betel nut and betel quid biomarkers in saliva, urine, and hair of betel consumers. Issue 10 (1st December 2015) - Franke, Adrian A.; Li, Xingnan; Lai, Jennifer F.
Abstract : Approximately 600 million people worldwide practise the carcinogenic habit of betel nut/quid chewing. Carcinogenic N‐nitroso compounds have been identified in saliva or urine of betel chewers and the betel alkaloid arecoline in hair from habitual betel quid chewers. However, the pharmacokinetic parameters of these compounds have been little explored. Assessment of betel use by biomarkers is urgently needed to evaluate the effectiveness of cessation programmes aimed at reducing betel consumption to decrease the burden of cancers in regions of high betel consumption. In the search for biomarkers of betel consumption, we measured by liquid chromatography‐mass spectrometry (LC‐MS) the appearance and disappearance of betel alkaloids (characteristic for betel nuts ), N‐nitroso compounds, and chavibetol (characteristic for Piper Betle leaves ) in saliva (n=4), hair (n=2), and urine (n=1) of occasional betel nut/quid chewers. The betel alkaloids arecoline, guvacoline, guvacine, and arecaidine were detected in saliva of all four participants and peaked within the first 2 h post‐chewing before returning to baseline levels after 8 h. Salivary chavibetol was detected in participants consuming Piper Betle leaves in their quid and peaked ~1 h post‐chewing. Urinary arecoline, guvacoline, and arecaidine excretion paralleled saliva almost exactly while chavibetol glucuronide excretion paralleled salivary chavibetol. No betel nut related compounds were detected in the tested hair samples using various extraction methods. From these preliminary results, we conclude that betel exposure can only be followed on a short‐term basis (≤8 h post‐chewing) using the applied biomarkers from urine and saliva while the feasibility of using hair has yet to be validated. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Appearance and disappearance pattern of arecoline, one of the main alkaloids characteristic for betel nuts in saliva and urine of betel chewers. Participant 1, 3 and 4 chewed a betel nut + Piper Betle leaves + lime for 5‐6 minutes, participant 2 chewed ¼ nut alone for 2.25 hours. Participant 1 also provided urine samples during and up to 48 hours after chewing. The alkaloids characteristic for the betel nut (arecoline, guvacoline, guvacine, arecaidine) were detected in saliva and peaked within the first 2 hours post‐chewing while salivary chavibetol, characteristic for the Piper Betel leaves, was detected in participants consuming Piper Betle leaves as part of their quid and peaked ~1 hour post chewing. Patterns of tested alkaloids and chavibetol in urine paralleled those in saliva. Saliva therefore reliably reflects systemic exposure to these agents. No betel nut/quid related compounds were detected in the tested hair samples.